SIMULATION KIT DISCHARGE LAMPS - THROTTLE IN MATLAB - , В. Ф.; , А. А. (Municipal economy of cities (Technical science), 2013)
The behavior of electrical parameters of the high pressure discharge lamp was investigated by computer simulation means. Results comparing with real measurements data confirm the used time-dependent processes model adequacy.